Clinical efficacy of various anti-hypertensive regimens in hypertensive women of Punjab; a longitudinal cohort study - Muhammad Umair; Mobasher Ahmad; Hamid Saeed; Zikria Saleem; Fatima Tauqeer (BMC, 2020)
Abstract Background Gender wise differences exist in anti-hypertensive treatment outcomes, yet still un-explored in Pakistan. Thus, we aimed to estimate the clinical efficacy of four different anti-hypertensive regimens in hypertensive women of Punjab, Pakistan. Methods A longitudinal cohort study of 12 months duration was conducted by enrolling 300 hypertensive women on four anti-hypertensive regimens. Chi-square for significance, logistic regression for association and multilevel regression for changes in outcomes were used. Results Majority of subjects were < 60 years of age, weighing > 65 Kg, having family history, married and hailing from urban areas, with diabetes as the most common comorbidity. Hypertension, adjusted for covariates, was significantly associated with salt intake (OR:2.27, p <  0.01) and physical activity (OR;2.16, p <  0.01). High-risk subjects, compared to low-risk, were consuming more fat (OR;1.54), meat (OR; 2), salt (OR; 2.48) and even vegetables/fruits (OR;3.43). Compared to baseline, the maximum reduction in BP was observed with combination therapy, N-GITS+LTN + HCT (SBP; − 50.17, p <  0.01, DBP; − 16.55, p <  0.01), followed by N-GITS alone (SBP; − 28.89, p <  0.01, DBP; − 12.21, p <  0.01). Compared to baseline, adjusted for treatment effects, significant reductions in SBP (low-risk ; − 17.92, p <  0.01 high-risk; − 19.48, p <  0.01) and DBP (low-risk; − 17.92, p <  0.01, high-risk; − 19.48, p <  0.01) were observed in low and high risk patients. Among all four cohorts, orthostatic hypotension and edema were common in N-GITS+LTN + HCT only, but variable effects were observed on biochemical values; urea, BSR and creatinine. Conclusion In conclusion, compared to a single agent, combination therapy conferred improved BP controls followed by N-GITS alone in low and high risk women with manageable side effects.